Unveiling the Impact of School Culture and Information Technology Usage on Teacher Performance: The Role of Work Motivation (Educational Management, 2022)
The purpose of this research was to investigate the ways in which school culture, information technology use, and teacher motivation all influence teacher performance, with teacher motivation serving as a mediating variable. The effectiveness of a teacher is measured by how well they carry out their job responsibilities, which include, but are not limited to, classroom management, planning, grading, and grading, as well as school administration, student counseling, and service delivery. School climate, information technology utilization, and educator motivation all have a role in how well teachers do their jobs. The research strategy used in this study is quantitative. There were a total of 110 teachers used for the study, all of them worked in public junior high schools in the Temanggung area. Cluster proportional sampling was used for the data collection. The questionnaire used as the study instrument was previously tested for its validity and reliability. In data analysis for hypothesis testing, path analysis and the Sobel test are used to examine potential mediating variables. Teachers' output is found to be affected by factors including school climate, information technology use, and job satisfaction. School culture and the use of technology serve as mediators between teachers' job motivation and students' learning outcomes. The conclusion is that the effect of independent variables on the dependent variable may be moderated by the effect of school culture and the use of information technology on teacher performance and work motivation